2020
DOI: 10.1002/aet2.10524
|View full text |Cite
|
Sign up to set email alerts
|

Mock Oral Board Examinations via Web‐based Video Teleconferencing in the Era of COVID‐19

Abstract: Owing to infection control measures necessitated by the COVID‐19 pandemic, many educational didactic components within residency programs have needed to adapt to virtual formats. We describe and evaluate the transition of an in‐person mock oral board certification examination to an entirely virtual format. Oral board cases consisting of two single cases and one triple case were adapted to a virtual format using a Web‐based video teleconferencing platform. Faculty examiners underwent 20‐minute training sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The learning curve for implementing the VCE was relatively brief, although perhaps not surprising in the COVID-19 era, with the widespread proliferation of electronic meetings. 1 , 3 The number of IT malfunctions was fairly small. However, it should be emphasized that these had been anticipated and that safeguards had been implemented to remediate them accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve for implementing the VCE was relatively brief, although perhaps not surprising in the COVID-19 era, with the widespread proliferation of electronic meetings. 1 , 3 The number of IT malfunctions was fairly small. However, it should be emphasized that these had been anticipated and that safeguards had been implemented to remediate them accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The positive-trending feedback of MOEs, especially those that are done virtually, in turn has led to an increased interest in the use of virtual platforms for administering MOEs. [7][8][9] MOEs are just one example of traditionally in-person events being shifted to a virtual paradigm due to the pandemic. Other educational forums, such as meetings and conferences, have had to adapt to the changing landscape of medical education, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual methods for medical trainee examination and assessment have become increasingly more prevalent due to COVID-19 and initial reviews have shown them to be adequate alternatives to traditional in-person educational paradigms. [8][9][10][11] The absence of major technological issues with administration of both the mock oral exam and recent vascular surgery oral board exam virtually is evidence of the practical utilization of alternative methods to in-person assessment and educational training. 6 As a result, some discrepancy between PDs and trainees in this study might represent different points of view instead of major issues with VMO per se.…”
Section: Limitationsmentioning
confidence: 99%
“…(1) to perform an initial assessment based on the Airways, Breathing, Circulation, Disability and Exposure approach, (2) to obtain an appropriate medical history based on the Allergy, Medications, Previous illness, Last meal and Event, (3) to formulate an initial management plan for the impending shock, (4) to recognize and manage hemodynamic deterioration, (5) to diagnose the cause of the instability and to plan appropriate actions for the management, (6) to communicate effectively the diagnosis and the plan to the patient.…”
Section: The European Board Examination In Emergencymentioning
confidence: 99%
“…This resulted in a reduction in the high expenditure related to organizing this examination face-to-face. The pandemic forced the movement of the oral component of the exam in the virtual modality, not only for EBEEM but even for American Board examination [5].…”
mentioning
confidence: 99%